Acupuncture for recurrent urinary tract infection in women: a systematic review and meta‐analysis. (3rd June 2020) - Qin, X; Coyle, ME; Yang, L; Liang, J; Wang, K; Guo, X; Zhang, AL; Mao, W; Lu, C; Xue, CC; Liu, X
Abstract : Background: Increasing antibiotic resistance has motivated interest in non‐antibiotic prophylaxis of recurrent urinary tract infections (rUTI). Objectives: To conduct a systematic review of the current state of evidence of acupuncture for uncomplicated rUTI in women. Search strategy: Nine databases (PubMed, Embase, CENTRAL, CINAHL, AMED, CBM, CNKI, CQVIP, Wanfang) were searched from inception to February 2019. Selection criteria: Randomised controlled trials (RCTs) evaluating the effects of acupuncture and related therapies for prophylaxis or treatment of uncomplicated rUTI in women were included. Data collection and analysis: Risk of bias was assessed, and the quality and strength of evidence evaluated using the GRADE framework. Results were reported as risk ratios (RR) for dichotomous outcomes or mean differences (MD) for continuous outcomes, with 95% confidence intervals (CI). Main results: Five RCTs involving 341 participants were included. Methodological quality of studies and strength of the evidence were low to moderate. The chance of achieving a composite cure with acupuncture therapies was greater than that with antibiotics (three studies, 170 participants, RR 1.92, 95% CI 1.31‐2.81, I 2  = 38%). The risk of UTI recurrence was lower with acupuncture than with no treatment (two studies, 135 participants, RR 0.39, 95% CI 0.26–0.58, I 2  = 0%) and sham acupuncture (one study, 53 participants, RR 0.45, 95% CI 0.22–0.92). Conclusions: Acupuncture appeared to be beneficial for treatment and prophylaxis of rUTIs, noting the limitations of the current evidence. Given the growing challenge of antibiotic resistance, there is a need for high‐quality RCTs of non‐pharmacological interventions such as acupuncture. Tweetable abstract: This review found that acupuncture may improve treatment and prevent recurrence of urinary tract infection in women. Tweetable abstract: This review found that acupuncture may improve treatment and prevent recurrence of urinary tract infection in women.